Perspectives on mental health recovery from Egyptian mental health professionals: A qualitative study. Issue 3 (13th April 2021) - Ibrahim, Nashwa; Ghallab, Eman; Ng, Fiona; Eweida, Rasha; Slade, Mike
Accessible Summary: What is known on the subject?: Personal recovery concept is dominant in mental health systems when service user involvement is emphasized; however, service user involvement in mental health research and practice does not exist in Egypt. Definitions of recovery from high‐income and English‐speaking countries should be carefully adapted to other settings. Nurses providing mental health care in Egypt generally do not have specialized mental health nursing qualifications. What the paper adds to existing knowledge?: Both cultural and contextual uniqueness of Egypt as a Middle Eastern, low‐middle‐income country were clear in the findings of this paper. There are differences in the definition of family and service user engagement in the current study and in high‐income countries. Seeking faith healers as a barrier to mental health recovery is culturally unique. Functional recovery prevails as a model in Egypt as there is limited service user involvement. Nursing values and code of ethics are consistent with enablers of mental health recovery. What are the implications for practice?: Changing the pre‐registration nursing education to prepare specialized graduates in mental health nursing. Training of mental health professionals on recovery approaches which involve service users is needed in Egypt. Mental health nurses in Egypt can use the current findings to implement national campaigns to raise public awareness of mental health problems. Abstract: Introduction: Recovery‐oriented mental health practice is an emerging approach that aims to empower individuals to define their goals and take responsibility for their own recovery. However, mental health practice in Egypt is still custodial. Aim: To explore perspectives of Egyptian mental health professionals on recovery. Method: Semi‐structured interviews were conducted with 15 mental health professionals identified through snowball sampling. Results: The current study identified that functional recovery outweighed other definitions. Four facilitators of mental health recovery were identified: therapeutic relationship; family engagement; cultural sensitivity; and professionals' self‐awareness. Six barriers to recovery were found, comprising mental health stigma and lack of awareness, seeking traditional healers, shortage of psychiatrists, cost of treatment, lack of training and effective rehabilitation programs. Discussion: The concept of functional recovery predominates among nurses and other mental health professionals, which may be due to limited training and the historical lack of service user involvement in Egypt. Lack of support from family and society, inadequate training MHPs and perceived system inefficiencies are also major impeding factors for recovery. Implications for Practice: There is a need for nurses to be involved in designing intervention programs targeting the general public and to support increased involvement of people with mental health issues.